2019
DOI: 10.3171/2018.9.peds18417
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of deep brain stimulation for the treatment of drug-resistant epilepsy in childhood

Abstract: OBJECTIVEDrug-resistant epilepsy (DRE) presents a therapeutic challenge in children, necessitating the consideration of multiple treatment options. Although deep brain stimulation (DBS) has been studied in adults with DRE, little evidence is available to guide clinicians regarding the application of this potentially valuable tool in children. Here, the authors present the first systematic review aimed at understanding the safety and efficacy of DBS for DRE in pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 44 publications
0
61
0
1
Order By: Relevance
“…Other targets have included the centromedian nucleus of the thalamus (CMT), the subthalmic nucleus (STN), the globus pallidus, the cerebellum, the hippocampus, the caudate nucleus and the seizure onset zone itself [59]. The CMT has been targeted for the treatment of generalized epilepsy [8,60,61,62,63,64,65]. A recent review by Li and Cook [59] summarized three small (largest sample size N = 9) randomized-controlled trials of stimulation of the hippocampus for mesial temporal lobe epilepsy, with all three showing a reduction in seizure frequency (15%–40%) versus placebo [66,67,68].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other targets have included the centromedian nucleus of the thalamus (CMT), the subthalmic nucleus (STN), the globus pallidus, the cerebellum, the hippocampus, the caudate nucleus and the seizure onset zone itself [59]. The CMT has been targeted for the treatment of generalized epilepsy [8,60,61,62,63,64,65]. A recent review by Li and Cook [59] summarized three small (largest sample size N = 9) randomized-controlled trials of stimulation of the hippocampus for mesial temporal lobe epilepsy, with all three showing a reduction in seizure frequency (15%–40%) versus placebo [66,67,68].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…There have been no randomized controlled trials for the use of DBS in pediatric patients with epilepsy. A recent systematic review identified case reports totaling 40 patients ages 4–18 who were treated with DBS for a variety of indications [60]. Five (12%) became seizure-free.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…Finally, these findings provide further support for the rapidly expanding field of neuromodulation for the treatment of focal epilepsy. In addition to Level I evidence for deep brain stimulation of the thalamus for treatment of epilepsy in adults (Fisher et al 2010), a recent systematic review of 40 children, many of them with focal pathology, also showed significant improvements with thalamic stimulation (Yan et al 2019). A focus on changes in impaired neural oscillations, both as biomarkers and targets of therapies, will be critical in the increasing application of neuromodulatory devices for epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…62 Deep brain stimulation targeted at the centromedian or anterior thalamic nuclei is an emerging treatment modality in refractory childhood epilepsies. 63 However, the stimulation of these nuclei, which are closely associated with the ascending arousal system, may lead directly to electroclinical arousals in a voltage-dependent manner. 64…”
Section: Influence Of Treatmentmentioning
confidence: 99%